Adaptive speed estimation of induction motor based on neural network inverse control - Aryza, Solly; Abdalla, Ahmed N.; Zulkeflee, Khalidin; Zulkarnain, Lubis (Elsevier Ltd, 2011)
The performance of the neural network based estimator is investigated with simulations for variations in the rotor resistance from their nominal values, with both speed and load torque disturbances.In this paper, adaptive speed control of induction motor using neural network inverse control scheme are proposed. The controller-structure design is based on a vector control scheme that transforms the three phase motor currents into flux and torque generating current components. The experiment results show that the proposed scheme has excellent dynamic and static control performance.